The illusion of the post-colonial state governance and security challenges in Africa - Fawole, W. Alade (African governance and development., 2018)
This broadly interdisciplinary book offers deep insight into Africa's colonial history for an understanding and explication of contemporary governance crises, security challenges, and state failure on the continent. It traverses political science, political economy, sociology, African history, and African studies in general.